Diuretic Activity of Sida cordifolia Linn. of Nilgiris - PRABHAKAR, T.; RAMESH, K.; NAGARATHNA, P.K.M.; SREENIVASA RAO, T.; LAKSHMAN, K.; SURESH, B. (Asian Journal of Chemistry, 2010)
The diuretic properties of petroleum ether, chloroform, ethyl acetate and methanol extract of roots of Sida cordifolia Linn. were evaluated by determination of urine volume, electrolyte concentration and diuretic potency in male albino rats. Different concentrations of petroleum ether, chloroform, ethyl acetate and methanol extract (250, 500 mg/kg) were orally administered to hydrated rats and their urine out put was immediately measured after 5 h of treatment. Furosamide (10 mg/kg) was used as reference drug while normal saline (0.9%) solution was used as control. All the extracts except petroleum ether extract exhibited dose dependent diuretic property. The onset of diuretic action was extremely prompt (within 1h) and lasted through out the studied period (upto 5 h). The chloroform, ethyl acetate, methanol extracts caused marked increase in Na+, K+ and Cl- level. The result of this experiment suggests that Sida cordifolia Linn. root extracts possessed significant diuretic activity in rats.